1993
DOI: 10.1254/jjp.63.151
|View full text |Cite
|
Sign up to set email alerts
|

Allergic Bronchospasm and Airway Hyperreactivity in the Guinea Pig

Abstract: ABSTRACT-In passively sensitized guinea pigs, slow infusion of an amount of ovalbumin insufficient to evoke airway obstruction induces hyperreactivity of the airways. A wide range of changed responsivity was observed for different test spasmogens, with leukotriene C4 > histamine > prostaglandin Fl, > bradykinin > leukotriene E4> serotonin > acetylcholine. Injection of ovalbumin as a bolus produced pronounced airway obstruction without hyperreactivity. Airway obstruction due to vascular engorgement (dextran inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 17 publications
2
5
0
Order By: Relevance
“…Excepting for diminished responses to LTC4 (reduced to 41 cm H2O/L/S, i.e. by 80%), closely similar values were recorded in normal animals after an interval (1 h) indicating that such measurements are sensitive detectors of changed airway reactivity [28].…”
Section: Differences In Basal Reactivity To Test Spasmogenssupporting
confidence: 67%
“…Excepting for diminished responses to LTC4 (reduced to 41 cm H2O/L/S, i.e. by 80%), closely similar values were recorded in normal animals after an interval (1 h) indicating that such measurements are sensitive detectors of changed airway reactivity [28].…”
Section: Differences In Basal Reactivity To Test Spasmogenssupporting
confidence: 67%
“…Although we did not determine this at the higher concentration of cetirizine more than 10 -6 g/ml (2.2 ! 10 -6 mol/l), the discrepancy between two drugs might be based on the difference of antihistamine effect: ketotifen is a non-competitive histamine antagonist in contrast to cetirizine, a competitive antihistamine [17,18]. In addition to our findings, a recent report showed that ketotifen at concentrations of 10 -6 and 10 -5 mol/l enhanced eosinophil peroxidase release induced not by fMLP but by C5a [19].…”
Section: Discussionsupporting
confidence: 48%
“…Airway sensitivity to histamine was not increased in our model, which is consistent with the studies cited earlier, which show that allergen challenge is required before AHR to histamine can be documented. This heterogeneity of AHR is well established and is characteristic of asthma ( O’Connor et al ., 1999 ) and animal models of hyper‐responsiveness ( Hoshiko & Morley, 1993 ).…”
Section: Discussionmentioning
confidence: 99%